Table of Content - -, (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content:1. An Analysis of the Impact of Digital Transformation on the Unemployment Rate in the Kingdom of Saudi Arabia during the period (2000-2021)Mrs. Fatimah Fahd Alateeg, Mrs. Abrar Adel Halawani2. The contribution of administrative information systems in providing services to trainees at the Institute of Public Administration in Riyadh, Kingdom of Saudi ArabiaMr. Ahmed Saud Alakeel3. The impact of digital transformation on the overall performance of The Ministry of Finance – GazaMrs. Israa Jomaa Ahmed Abu Lehea4. The role of diplomatic means in the settlement of international disputesMr. El-Moatazbellah Mohamed Mohamed Noureldin5. Measuring the quality of services provided by Mobily and its impact on the satisfaction  of the pilgrimsMr. Saleh Matrouk Hamed Alosaimi6. Measuring the Impact of Economic Variables on the Stock Market in Saudi Arabia: An Analytical Study from 2000 – 2021Mr. Ahmad Saeed Basilim, Dr. Basel Yasser Balila7. Economic factors affecting rice imports in Kingdom of Saudi Arabia during the period  from (1989-2018)Mrs. Buthaynah Hashim Al-Hassan, Co-Prof. Samar S. Mohamed Abdalla, Co-Prof. Raga M. Elzaki9. Convergence between the Marketing System & AI (The beginnings of the IR 5.0 & the birth of Algorithmic Marketing Age)Co-Prof. Tarek Ahmed Guendouz
Keywords: Journal of Economic, Administrative and Legal Sciences